Complicated lateral ventral hernia: tomographic diagnosis - Piñeyro, Alberto; Albo, Manuel; Crosa, Jorge; Albo, Daniel (Cirugía del Uruguay, 1994)
A case of complicated lateral ventral hernia diagnosed by means of computerized tomography is presented. The authors analyse anatomical, clinical, diagnostica/ and therapeutical aspects fo this pathology with special emphasis on paraclinical tests.